2020
DOI: 10.1093/jisesa/ieaa040
|View full text |Cite
|
Sign up to set email alerts
|

Attractiveness of Cattle Dung to Coprophilous Beetles (Coleoptera: Scarabaeoidea and Sphaeridiinae) and Their Segregation During the Initial Stages of the Heterotrophic Succession on a Pasture in Southeast Michigan

Abstract: Only a few mostly older studies analyzed the heterotrophic succession of dung beetles in the Midwestern United States. Such studies are needed to track the impacts of the climate crisis on heterotrophic succession and the associated decomposition processes that are central to soil fertility and carbon sequestration. The current study closes this knowledge gap and provides an easy and efficient method to estimate the relative attractiveness of individual dung pads during heterotrophic succession. The dung beetl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 63 publications
0
16
1
Order By: Relevance
“…(2) Succession (exposure time) from the pooled 15 pitfall traps collected after 2 days exposure and a pooled late sample collected after 3 days. Analyses of these data were published in Wassmer (2020).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…(2) Succession (exposure time) from the pooled 15 pitfall traps collected after 2 days exposure and a pooled late sample collected after 3 days. Analyses of these data were published in Wassmer (2020).…”
Section: Discussionmentioning
confidence: 99%
“…Since 2013, the cattle are moved to a larger more productive pasture in mid to late spring and are replaced by a small herd of goats, a pony, and a donkey; cattle return to the farm in late autumn. More details about the study site can be found in Wassmer (2020).…”
Section: Locationmentioning
confidence: 99%
See 3 more Smart Citations